Analysis of the factors affecting the intention of accounting students in STIE Perbanas Surabaya to use Mandiri Internet Banking - Hana Pratiwi (STIE Perbanas Surabaya, 2016)
This study attempts to see the effect of perceived usefulness, ease of use, trust, service quality, and computer anxiety on the intention of accounting students in STIE Perba-nas Surabaya to use Mandiri internet banking. The population is all Accounting Students of STIE Perbanas Surabaya with the sample from Accounting Students (Bachelor Degree) of STIE Perbanas Surabaya. They were taken by using a purposive sampling method, with the criteria of the respondents in batch year of 2011-2014. The independent variables in this study are perception usefulness, perceived ease of use, perceived trust, perceived Service quality and Computer Anxiety, while the dependent variable is the intention of accounting students of STIE Perbanas Surabaya to use Mandiri internet banking. The research method used is quantitative, with primary data obtained from questionnaires. The data analysis technique used is multiple linear regression analysis. The results of this study indicate that the variables of perception usefulness, ease of use, trust, and service quality have significant effect on the inten-tion of accounting students of STIE Perbanas Surabaya to use Mandiri internet bank-ing either simultaneously or partially, but the variable of perceived computer anxiety partially has no significant effect on the intention of accounting student of STIE Per-banas Surabaya to use Mandiri internet banking.